1993
DOI: 10.1007/bf02244646
|View full text |Cite
|
Sign up to set email alerts
|

The benzodiazepine antagonist flumazenil blocks the effects of CCK receptor agonists and antagonists in the elevated plus-maze

Abstract: Peripheral administration of the unsulphated cholecystokinin octapeptide (CCK-8us) led to an anxiogenic-like action in the elevated plus-maze model of anxiety in rats. Devazepide and L-365,260 showed potent anxiolytic-like effects at similar doses. The fact that devazepide is 1000 times more potent as a CCK-A receptor antagonist than L-365,260, whereas the two compounds are nearly equipotent at the CCK-B receptor subtype, suggests that CCK-B rather than CCK-A receptors are involved in these effects. Similar re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 33 publications
6
17
0
Order By: Relevance
“…Consequently, it is likely that the behavioral responses to di¤erent anxiogenic stimuli are di¤erentially a¤ected by similar doses of the same anxiolytic agent. This hypothesis is sustained by other Þndings, showing that the minimum e¤ective dose may vary among animal model predictive of anxiolysis (Chopin and Briley 1993;Griebel et al 1994;Wieland et al 1995;Singh et al 1996).…”
Section: Discussionmentioning
confidence: 43%
“…Consequently, it is likely that the behavioral responses to di¤erent anxiogenic stimuli are di¤erentially a¤ected by similar doses of the same anxiolytic agent. This hypothesis is sustained by other Þndings, showing that the minimum e¤ective dose may vary among animal model predictive of anxiolysis (Chopin and Briley 1993;Griebel et al 1994;Wieland et al 1995;Singh et al 1996).…”
Section: Discussionmentioning
confidence: 43%
“…It has earlier been shown that CCK B receptor antagonists (L-365 260) can block the anxiogenic effects of CCK8 in animal models (Chopin and Briley 1993), and that of CCK4 (Bradwejn et al 1994) and pentagastrin (Lines et al 1995) in human studies. De Montigny describes panicogenic action of CCK4 in healthy individuals, panic attacks being provoked in doses ranging from 20 to 100 µg (de Montigny 1989).…”
Section: Cck B Receptors and Discomfortmentioning
confidence: 42%
“…In contrast, the selective CCK 2 agonist, CCK-4, induces anxiety in nonhuman subjects [20,305] and promotes panic in panic patients and normal subjects [21,23]. The differential propensity of CCK-8S and CCK-4 to provoke anxiety and/or panic in human subjects as well as rats and mice may be attributable to species variations [306], differential brain region sensitivity (e.g., amygdala, prefrontal cortex and nucleus accumbens, [307,308]), drug route [309,310] and/or paradigm specificity [308]. Clearly, discrepancies between clinical and nonhuman studies necessitate examination of methodological variables including drug schedule and experiential factors that influence sensitivity to CCK challenge and anxiety (panic) induction.…”
Section: Cholecystokinin Anxiety and Panic Attackssupporting
confidence: 41%
“…In rats, flumazenil (4 mg/kg i.p.) significantly antagonized the anxiogenic effects of the CCK 2 agonist, CCK-8S and the anxiolytic-like effects of the CCK 2 antagonist, L-365, 260 [310]. Moreover, rats rated anxious with respect to performance in the elevated plus maze exhibited a reduced benzodiazepine receptor density and increased CCK-8S binding in the frontal cortex relative to non-anxious counter-parts [315].…”
Section: Cholecystokinin Induced Anxiety: Nonhuman Modelssupporting
confidence: 41%